Contrast-enhanced ultrasound using real-time contrast harmonic imaging in invasive breast cancer: comparison of enhancement dynamics with three different doses of contrast agent. (January 2015) - Saracco, Ariel; Szabó, Botond K; Aspelin, Peter; Leifland, Karin; Tánczos, Ervin; Wilczek, Brigitte; Axelsson, Rimma
Background: In the last few years new potential applications have been developed for contrast-enhanced ultrasound (CEUS) and the management of breast diseases, but there is still some debate concerning the optimal dose to evaluate breast lesions, especially as a diagnostic tool. Purpose: To compare different CEUS doses of injected contrast agent in order to establish an optimal dose for the diagnosis of invasive breast cancer. Material and Methods: In Group A we compared the bolus dose of 1.2 mL vs. 2.4 mL and in Group B we compared the bolus dose of 2.4 mL vs. 4.8 mL (26 and 25 invasive carcinomas, respectively). CEUS was performed in real-time contrast harmonic imaging (CHI) using a L9-3 MHz probe. All examinations were recorded in a contrast side/side imaging mode loop for 120 s. Wash-in and wash-out patterns of the contrast agent were analyzed with advanced US quantification software and kinetic curves were used for statistical analysis. Results: In Group B (2.4 mL vs . 4.8 mL), more and stronger correlation was found among kinetic parameters (area under the curve, P < 0.00001; lognormal model parameters, μ, P = 0.0007 and σ, P < 0.0001; mean transit time, P < 0.0001; model-based wash-out ratios, W21m, P = 0.0002; W50m, P = 0.0001; time-to-peak, P = 0.005) as compared to Group A (1.2 mL vs . 2.4 mL). Conclusion: The optimal way to evaluate kinetic features of invasive breast tumors using real-time CEUS is with an injection of contrast agent of either 2.4 mL or 4.8 mL.